1988
DOI: 10.1016/s0140-1971(88)80034-4
|View full text |Cite
|
Sign up to set email alerts
|

Ego identity: Developmental differences and experimental substance use among adolescents

Abstract: A total of 12,988 adolescents completed a questionnaire which assessed experience with cigarettes, inhalants, alcohol, marijuana, cocaine, and level of ego identity (EOM‐EIS). Discriminant analyses of substance use, across the achievement, moratorium, foreclosure, and diffusion identity statuses, yielded significant functions for each grade comparison (7th to 12th). Frequencies of experience for diffused respondents were consistently higher than estimates for the achieved and moratorium respondents; and, forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
2
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 27 publications
6
51
2
2
Order By: Relevance
“…It has been hypothesized that identity confusion increases adolescents' proneness to aggression, delinquency, and other forms of deviant behavior (Jones, 1992(Jones, , 1994). These expectations have been supported in past research (e.g., Jones & Hartmann, 1988;Jones et al, 1989).…”
Section: Identity As a Positive Developmental Processsupporting
confidence: 61%
See 1 more Smart Citation
“…It has been hypothesized that identity confusion increases adolescents' proneness to aggression, delinquency, and other forms of deviant behavior (Jones, 1992(Jones, , 1994). These expectations have been supported in past research (e.g., Jones & Hartmann, 1988;Jones et al, 1989).…”
Section: Identity As a Positive Developmental Processsupporting
confidence: 61%
“…It has been hypothesized that identity confusion increases adolescents' proneness to aggression, delinquency, and other forms of deviant behavior (Jones, 1992(Jones, , 1994). These expectations have been supported in past research (e.g., Jones & Hartmann, 1988;Jones et al, 1989).The way in which identity is measured may have important implications for its role in the relationship between family functioning and behavior problems during early adolescence. The identity status model (Marcia, 1966(Marcia, , 1980 see Berzonsky & Adams, 1999;Waterman, 1999, for recent reviews) is by far the most widely accepted and studied empirical extension of Erikson's identity stage.…”
mentioning
confidence: 75%
“…When compared with identity achievement, identity diffusion had more recently been shown to be associated with conformity and susceptibility to peer pressure (Adams, Ryan, Hoffman, Dobson & Nielsen, 1985) and more manipulative behaviour, at least in a small group setting (Read, Adams & Dobson, 1984), Within adolescent populations, such findings should not, however, lead to an unqualified equating of full achievement status with psychological health. Whereas Jones and Hartmann (1988) found adolescents with identity diffusion to be most likely of all to abuse drugs and alcohol, those adolescents with moratorium and achievement status were also more likely to abuse substances than were those with foreclosure (perhaps because the latter had unquestionably adopted parental standards or proscriptions). Rotheram-Borus (1989) discovered higher levels of anxiety, inattentiveness and behaviour problems among adolescents with moratorium and achievement status compared with foreclosure and diffusion.…”
Section: Associations With Mental Healthmentioning
confidence: 95%
“…In cross-sectional studies, identity has been shown to be inversely related to both substance use (Jones & Hartmann, 1988;Jones, Hartmann, Grochowski, & Glider, 1989) and unsafe sex (Hernandez & DiClemente, 1992). These studies have suggested that identity may serve as a protective mechanism against these health risk behaviors.…”
Section: Health Risk Behaviors and Psychological Problemsmentioning
confidence: 99%